Permeability of Cork for Water and Ethanol - Fonseca, Ana Luisa; Brazinha, Carla; Pereira, Helena; Crespo, João G.; Teodoro, Orlando M. N. D. (Journal of Agricultural and Food Chemistry, 2013)
Transport properties of natural (noncompressed) cork were evaluated for water and ethanol in both vapor and liquid phases. The permeability for these permeants has been measured, as well as the sorption and diffusion coefficients. This paper focuses on the differences between the transport of gases? relevant vapors and their liquids (water and ethanol) through cork. A transport mechanism of vapors and liquids is proposed. Experimental evidence shows that both vapors and liquids permeate not only through the small channels across the cells (plasmodesmata), as in the permeation of gases, but also through the walls of cork cells by sorption and diffusion as in dense membranes. The present study also shows that cork permeability for gases was irreversibly and drastically decreased after cork samples were exposed to ethanol or water in liquid phase.
doi: 10.1021/jf4015729doi: 10.1021/jf4015729The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; diffusion; permeability; sealing properties; Sorption; water transport

Wine Oxidation and the Role of Cork - Karbowiak, Thomas; Gougeon, Régis D; Alinc, Jean-Baptiste; Brachais, Laurent; Debeaufort, Frédéric; Voilley, Andrée; Chassagne, David (Critical Reviews in Food Science and Nutrition, 2009)
The present review aims to show the state of the art of oxidation mechanisms occurring especially in white wines by taking into account knowledge from different fields in relation to the subject. It is therefore divided into three main parts. First, the mechanisms of oxidation relevant to white wine are discussed in the light of recent scientific literature. Next, the phenomenon of oxygen solubility in wine during the winemaking process, and in particular during bottling is stated theoretically as well as practically. Finally, the aspect of wine conservation after bottling is examined with respect to mass transfers which may occur through the closure, with a special emphasis on cork. Currently, specific physico-chemical properties still make cork closures the most important closure type used for the wine market, and especially for high quality wines. This final section will also include a review of studies performed on this subject, which have been analyzed in detail from a theoretical mass transfer point of view, in order to assess the extent to which the proposed scientific tools and the observed tendencies are relevant to progress in the understanding of the impact of this parameter on the behavior of a wine.
doi: 10.1080/10408390802248585
Keywords: Cork; diffusion; Oxygen; permeability; phenolic compounds; solubility; white wine